PENERAPAN METODE FULL COSTING DALAM PENETAPAN HARGA POKOK PRODUKSI PADA USAHA KECIL MENENGAH - vitratin vitratin (Universitas Malahayati, 2018)
This study aims to determine whether the fullcosting method is more effective to use bySMEs compared to the manual calculations performed by SMEs. The method used is by calculatingthe cost of production to determine the selling price with the Full Costing approach, namely the totalcost of production divided by the selling price multiplied by 100%. .Keywords: Full costing method, selling price